Peculiarities of Speed Qualities Development in Young Fencers Using Modern Active Games - І. В. Кривенцова; С. А. Пашкевич; В. К. Хавалджи (OVS LLC, 2015)
Research objective: to evaluate the effectiveness of the developed and grounded methods of implementing active games in the training process of 12-14-year-old fencers in order to improve their speed qualities. Methods. The 12-14-year-old fencers of the "Unifekht" Sports Club (10 - test group (TG), 10 - reference group (RG)) participated in the forming experiment for three months. The TG introduced active games in the training process, the RG kept training under the standard program. We evaluated the effectiveness by the changes in the parameters of speed reactions and the evaluation of the tactical abilities and the speed of tactical training. The rough evaluation of the cause-effect relationship between the influencing factor and the effect appearance rested on Spearman's rank correlation coefficient (r) used in the study. We compared the initial characteristics between the groups using the χ2 tests (binary variables), Mann-Whitney test to compare the distribution of ordinal variables, and Wilcoxon test (related samples). Results. The three months of the implemented game methods of speed qualities development allowed to establish a probable increase in the lability indicators of the nervous system of the TG fencers (P < 0.05). However, the stress resistance indicators tended to decrease the dynamics when compared to the RG indicators. The indicator definitely responding to the methods was evaluation of the tactical abilities and the speed of tactical training. The latter increased both in the experiment dynamics and in comparison with the evaluation of the RG (p < 0.05). The evaluation of the effectiveness of the game method pursuant to the dynamics of the speed qualities indicators of the young fencers allowed to objectively prove the importance of games in speed development in the training process.